Bentuk Dan Mekanisme Pemberdayaan Oleh Asosiasi Petani Tembakau Indonesia (APTI) Guna Mendukung Ketahanan Ekonomi Petani Tembakau di Kabupaten Temanggung, Jawa Tengah - Nuryanti Nuryanti; Subejo Subejo; Budi Guntoro (Jurnal Ketahanan Nasional, 2018)
ABSTRACTIndonesian Tobacco Farmers Association (APTI) was an organization which was formed for facilitating tobacco farmers. This association had been conducting various efforts on farmer empowerment.This research was aimed to described the forms and mechanism of tobacco farmer’s empowerment developed by the APTI Temanggung to supported economic resilience’s farmer,This study used mixed research methods, with strategy of concurrent embedded (qualitative and quantitative method).The research results showed that there were 4 (four) programs which were successfully established and implemented by APTI Temanggung, namely (a). the empowerment program of APTI Central Java chapter to took care of farmers’ education, (b). Business Credit for Tobacco Farming (KUMPT) program, (c). mentoring, coaching and assisting tobacco farmers program, and (d). the main developmental program of APTI to advocated farmers about tobacco’s regulation. All forms of empowerment done by APTI were facilitated by using different empowerment mechanism for each program.ABSTRAK Asosiasi Petani Tembakau Indonesia (APTI) sebagai organsiasi dengan tujuan untuk memfasilitasi petani tembakau dengan melakukan berbagai upaya pemberdayaan petani. Penelitian ini bermaksud untuk menggambarkan bentuk dan mekanisme pemberdayaan petani tembakau yang dikembangkan oleh (APTI) Temanggung guna mendukung ketahanan ekonomi petani tembakau. Penelitian ini menggunakan mixed methods dengan strategi embedded konkuren (kualitatif dan kuantitatif).Hasil penelitian menunjukkan bahwa program-program pemberdayaan yang berhasil dibentuk dan dilaksanakan APTI Temanggung ada 4 (empat) yaitu (a) program pemberdayaan APTI DPD Jateng peduli pendidikan, (b) program Kredit Usaha Mandiri Pertanian Tembakau (KUMPT), (c) program pembimbingan pembinaan dan pendampingan petani tembakau, dan (d) program pemberdayaan utama APTI adalah advokasi regulasi pertembakauan. Semua bentuk pemberdayaan yang dilakukan APTI Temanggung adalah fasilitasi dengan mekanisme tiap program berbeda-beda.